Manajemen Kurikulum dan Sistem Penilaian di Sekolah Tinggi Pariwisata Bandung - Wahyudin; Hanafiah; Supena, Agus Nana (Sekolah Tinggi Agama Islam Babussalam Sula, 2021)
This journal aims to find out how the Bandung Tourism College in the implementation of the curriculum management system and assessment has been running according to procedures and even supervised directly from the Central Ministry of Tourism, this makes STP Bandung a Tourism College which has a big name in the field of tourism in Indonesia. In particular, this study aims to obtain information and empirical analysis of: 1) learning management at STP Bandung. 2) curriculum at STP Bandung 3) assessment of learning at STPB Bandung.